A body at the book fair - Alexander, Ellie (Alexander, Ellie. Secret bookcase mystery, 2025)
In the gripping conclusion to The Secret Bookcase series, Annie Murray races to untangle the ultimate plot twist, Life is good for Annie. She's found healing at the Secret Bookcase, her beloved Agatha Christie-themed mystery bookstore in the cozy town of Redwood Grove and is on the brink of launching her very own detective agency. But she's still haunted by one unsolved case, the murder of her best friend Scarlet ten years ago. When Annie heads to Santa Clara for their annual book fair, she's looking forward to meeting fellow booklovers. And she's also got a secret mission: she'll be close to Silicon Summit Partners, the powerful investment firm she just knows had a hand in Scarlet's death. But when an industry colleague is murdered at the book fair, Annie is first on the scene to investigate. The suspect list reads like a book lover's who's who, a celebrity author with a suspicious agenda, a rival with a grudge, and even a kindly grandmother pursuing her lifelong dream of owning a bookstore. With her fellow bookseller and crime-fighting partner Fletcher playing Watson to her Holmes, can Annie catch the killer before they strike again? And will it distract her from her mission to finally bring her best friend Scarlet's murderer to justice?.--